Loss of DJ-1 elicits retinal abnormalities, visual dysfunction, and increased oxidative stress in mice. (October 2015) - Bonilha, Vera L.; Bell, Brent A.; Rayborn, Mary E.; Yang, Xiaoping; Kaul, Charlie; Grossman, Gregory H.; Samuels, Ivy S.; Hollyfield, Joe G.; Xie, Chengsong; Cai, Huaibin; Shadrach, Karen G.
Abstract: DJ-1/PARK7 mutations or deletions cause autosomal recessive early onset Parkinson's disease (PD). Thus, DJ-1 protein has been extensively studied in brain and neurons. PD patients display visual symptoms; however, the visual symptoms specifically attributed to PD patients carrying DJ-1/PARK7 mutations are not known. In this study, we analyzed the structure and physiology of retinas of 3- and 6-month-old DJ-1 knockout (KO) mice to determine how loss of function of DJ-1 specifically contributes to the phenotypes observed in PD patients. As compared to controls, the DJ-1 KO mice displayed an increase in the amplitude of the scotopic ERG b-wave and cone ERG, while the amplitude of a subset of the dc-ERG components was decreased. The main structural changes in the DJ-1 KO retinas were found in the outer plexiform layer (OPL), photoreceptors and retinal pigment epithelium (RPE), which were observed at 3 months and progressively increased at 6 months. RPE thinning and structural changes within the OPL were observed in the retinas in DJ-1 KO mice. DJ-1 KO retinas also exhibited disorganized outer segments, central decrease in red/green cone opsin staining, decreased labeling of ezrin, broader distribution of ribeye labeling, decreased tyrosine hydroxylase in dopaminergic neurons, and increased 7, 8-dihydro-8-oxoguanine-labeled DNA oxidation. Accelerated outer retinal atrophy was observed in DJ-1 KO mice after selective oxidative damage induced by a single tail vein injection of NaIO3, exposing increased susceptibility to oxidative stress. Our data indicate that DJ-1-deficient retinas exhibit signs of morphological abnormalities and physiological dysfunction in association with increased oxidative stress. Degeneration of RPE cells in association with oxidative stress is a key hallmark of age-related macular degeneration (AMD). Therefore, in addition to detailing the visual defects that occur as a result of the absence of DJ-1, our data is also relevant to AMD pathogenesis. Highlights: First report of the visual defects due to the absence of DJ-1 expression in mice retinas. DJ-1 KO mice displayed increased b-wave amplitude and cone ERGs, and decreased dc-ERG amplitude. DJ-1 KO retinas displayed structural changes in the outer plexiform layer, photoreceptors and retinal pigment epithelium. DJ-1-deficient retinas changes are associated with increased oxidative stress.